Descriptive epidemiology of COVID-19 deaths in the North Indian district Kangra of Himachal Pradesh - Rattan, Saurabh; Sharma, Priya; Gupta, Chahat; Katoch, Vikram; Gupta, Gurdarshan (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 first reported in January 2020 in China has turned into a pandemic the kind that occurs only once in a century, with high mortality rate due to an infectious disease considered once as a thing of past. Caused by SARS-CoV-2 (an RNA virus) COVID-19 has caused over 170 million cases worldwide and around 3.8 million deaths worldwide. India alone has suffered the wrath of this nasty virus with cases approaching 30 million and over 0.4 million deaths till date. Occurring in various waves, the pandemic situation remains dynamic and evolving even today. Methods: We carried out retrospective analysis of all deaths due to COVID-19 occurring in district Kangra from March 2020 to June 2021. Descriptive data on all COVID-19 patients were collected and analysed including individuals who lost their life during the period. Results: From 20 March 2020 to 30 June 2021, a total of 45,871 cases and 1037 deaths (2.2%) were reported in Kangra district-33.8% of 3463 deaths that occurred in the entire state. The death rate per million population in Kangra was 64 compared to 47 for Himachal Pradesh and 30 for India as a whole. The mean age was 62.5 years (range 01 to 102 years); males 62.7 years and female 62.2 years. Conclusions: The biggest challenge for us as a country is that COVID-19 has penetrated into our densely placed population where practicing COVID-19 appropriate behaviour is merely an expectation that possibly can never be fulfilled despite most stringent of actions.